Wheat quality improvement at CIMMYT and the use of genomic selection on it - Guzman, C.; Pena, R. J.; Singh, R.; Autrique, E.; Dreisigacker, S.; Crossa, J.; Rutkoski, J.; Poland, Jesse A.; Battenfield, S. (My University, 2016)
The International Center for Maize and Wheat Improvement (CIMMYT) leads the Global Wheat Program, whose main objective is to increase the productivity of wheat cropping systems to reduce poverty in developing countries. The priorities of the program are high grain yield, disease resistance, tolerance to abiotic stresses (drought and heat), and desirable quality. The Wheat Chemistry and Quality Laboratory has been continuously evolving to be able to analyze the largest number of samples possible, in the shortest time, at lowest cost, in order to deliver data on diverse quality traits on time to the breeders formaking selections for advancement in the breeding pipeline. The participation of wheat quality analysis/selection is carried out in two stages of the breeding process: evaluation of the parental lines for new crosses and advanced lines in preliminary and elite yield trials. Thousands of lines are analyzed which requires a big investment in resources. Genomic selection has been proposed to assist in selecting for quality and other traits in breeding programs. Genomic selection can predict quantitative traits and is applicable to multiple quantitative traits in a breeding pipeline by attaining historical phenotypes and adding high-density genotypic information. Due to advances in sequencing technology, genome-wide single nucleotide polymorphism markers are available through genotyping-by-sequencing at a cost conducive to application for genomic selection. At CIMMYT, genomic selection has been applied to predict all of the processing and end-use quality traits regularly tested in the spring wheat breeding program. These traits have variable levels of prediction accuracy, however, they demonstrated that most expensive traits, dough rheology and baking final product, can be predicted with a high degree of confidence. Currently it is being explored how to combine both phenotypic and genomic selection to make more efficient the genetic improvement for quality traits at CIMMYT spring wheat breeding program. (C) 2016 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
Citation: Guzman, C., Pena, R. J., Singh, R., Autrique, E., Dreisigacker, S., Crossa, J., . . . Battenfield, S. (2016). Wheat quality improvement at CIMMYT and the use of genomic selection on it. Applied and Translational Genomics, 11, 3-8. https://doi.org/10.1016/j.atg.2016.10.004
Keywords: Wheat Quality; Genomic Selection; Wheat Breeding; Bread-Making Quality; Quantitative Traits; Molecular Markers